(untitled) (Economics and region, 2016)
The methods of planning company’s financial indicators and the economic and mathematical optimization models used in financial planning was researched in the article. In the practice of financial planning used such methods: normative, balance of payment, the cash flows of multiple, economic and mathematical modelling, optimization of planning decisions and economic analysis. The software for the planned of financial indicators were analysed. The most convenient and affordable to use program were determined. One of directions of financial planning at the enterprise is the SAP software, which automates the process of planning, forecasting, budgeting, levelling information and financial risks. The SAP system consists of a set of application modules that support various business processes and integrated with each other in real time. We present the results of the planning of revenues, costs and financial results of the operating enterprise by using the software platform CurveExpert 1.3.